2011
DOI: 10.1590/s0104-42302011000600018
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hypertensive disorders of pregnancy in Southern Brazil

Abstract: The risk factors associated with hypertensive disorders in pregnancy appear to be similar to those reported in other countries. The knowledge of the risk factors could be helpful in a prenatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
14
2
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 36 publications
7
14
2
7
Order By: Relevance
“…There was no significant association between the study outcome and the skin color / race, diverging from other studies 16,25,27,28 which observed statistical significance among black women. For the use of tobacco during gestation, the results of the present study ratify researches carried out at the national level, in Maternities of the States of the Northeast, 19 Southeast 23 and Southern Regions of Brazil, 23 as well as with research data from other countries with women of Nordic countries 26 (Sweden, Norway, Denmark, Finland and Iceland), since no significant associations were found.…”
Section: Modelscontrasting
confidence: 99%
See 2 more Smart Citations
“…There was no significant association between the study outcome and the skin color / race, diverging from other studies 16,25,27,28 which observed statistical significance among black women. For the use of tobacco during gestation, the results of the present study ratify researches carried out at the national level, in Maternities of the States of the Northeast, 19 Southeast 23 and Southern Regions of Brazil, 23 as well as with research data from other countries with women of Nordic countries 26 (Sweden, Norway, Denmark, Finland and Iceland), since no significant associations were found.…”
Section: Modelscontrasting
confidence: 99%
“…It was verified that the women who had some disease before the pregnancy presented a 21 times higher chance to develop some type of SGHS when compared to those that did not present previous disease. These findings agree with a study conducted in the Southern Region of Brazil by Dalmáz et al, 25 who found, in the multivariate analysis, an association between SGHS and chronic hypertension and non-gestational diabetes, showing that chronic hypertension and non-gestational diabetes, increases in seven times and in three times, respectively, the chance to develop (OR = 7.05, CI95%= 1.99 -24.93, OR = 3.87, CI95%= 1. 22 -12.27).…”
Section: Modelssupporting
confidence: 94%
See 1 more Smart Citation
“…Por sua vez, a ocorrência da HG mostrou associação a partir do 2º trimestre com elevação dos níveis pressóricos conforme observado em outros estudos (5,8) . Os riscos advindos do aumento pressórico configuram-se em distúrbios de origem circulatória, além de fator de risco para sobrevida neonatal (16) .…”
Section: Iresultadosunclassified
“…As características definidoras são um conjunto de evidências que se agrupam como manifestação dos sinais e sintomas que asseguram a presença de um determinado diagnóstico, enquanto que os fatores relacionados, são aqueles que se constituem como a etiologia desse diagnóstico, ou seja, determinam as causas da origem de um determinado fenômeno (8) .…”
unclassified